Erasmus students in Portugal: from students to tourists and advocates - Amaro, Suzanne (2019)
Although there are several studies examining the benefits of the Erasmus student mobility programme on student’s professional career and academic development, there is scarce literature focusing on how they are similar to tourists and can promote tourism in the country where they did Erasmus. This study interviewed 16 students from 10 different nationalities that have done Erasmus in Portugal, in order to examine their travelling behaviours and how they may contribute in promoting Portugal. The findings reveal that Erasmus students are similar to tourists, contributing to Portugal’s Tourism not only by their travelling behaviour, but also by the visitors they receive and because of the posts of Portugal on social media. Furthermore, after their Erasmus experience, they become advocates, recommending Portugal to family and friends.